UTILIZATION OF BLONDOS STONE ON POROUS CONCRETE - Ginting, Arusmalem; Suyono (Jurnal Teknik Sipil, 2022)
Porous concrete can be used as a drainage system that allows rainfall to percolate into the ground, reduce stormwater runoff, and recharge groundwater. Porous concrete consists of coarse aggregate and cement paste. Stone mining waste in the river, namely medium-sized gravel which is often called blondos stone, has not been used optimally as a building material. Based on these reasons, it is tried to use blondos stone as coarse aggregate in porous concrete. Three variations of the gravel-cement ratio were used, that is: 4, 5, and 6, and 3 variations of the water-cement ratio, that is: 0.30, 0.35, and 0.40. There are 27 specimens of porous concrete cylinders, and each variation consists of 3 specimens. Permeability and compressive strength testing after 28 days of curing. The conclusions of this study are: increasing the water-cement ratio and gravel-cement weight ratio decreases the compressive strength and increases the permeability of the porous concrete. The water-cement ratio and gravel-cement weight ratio have no significant effect on the density of porous concrete. Blondos stone is adequate to be used for the manufacture of porous concrete.